2019
DOI: 10.1021/acsami.9b12748
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Performance of Zintl Phase Ca9Zn4+xSb9 by Beneficial Disorder on the Selective Cationic Site

Abstract: Zintl phase compounds Ca 9 Zn 4+x Sb 9 have promising thermoelectric properties due to their complex crystal structure and tunable interstitial Zn. In this work, we prepared nominal Ca 9 Zn 4+x Sb 9 (x = 0.5, 0.6, 0.7, and 0.8) using ball milling and hot pressing. Further decreased lattice thermal conductivity was obtained by isoelectronic substitution of Eu on the selective Ca site, which is farther away from the framework of [Zn 4+x Sb 9 ] δ− for the smaller disturbance of carrier transport. Together with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…In the structures of the Zintl-phase compounds, the anionic framework is responsible for electrical conduction and that the cations provide a way of tuning electrical properties and providing phonon scattering. Up to now, Zintl-phase TE materials can be roughly classified into the 14-1-11 type, , 1-2-2 type, , 3-1-3 type, , 5-2-6 type, , 9-4.5-9 type, , and so forth. In addition, the ZrBeSi-type Zintl-phase compound (such as KZnSb, Sr 2 ZnP 2 , etc. )…”
Section: Introductionmentioning
confidence: 99%
“…In the structures of the Zintl-phase compounds, the anionic framework is responsible for electrical conduction and that the cations provide a way of tuning electrical properties and providing phonon scattering. Up to now, Zintl-phase TE materials can be roughly classified into the 14-1-11 type, , 1-2-2 type, , 3-1-3 type, , 5-2-6 type, , 9-4.5-9 type, , and so forth. In addition, the ZrBeSi-type Zintl-phase compound (such as KZnSb, Sr 2 ZnP 2 , etc. )…”
Section: Introductionmentioning
confidence: 99%
“…Only 12 ternary compounds from A –Zn–Sb ( A = alkali metal) systems can be found in the Inorganic Crystal Structure Database (ICSD) and literature: LiZnSb, Li 2 ZnSb, NaZnSb, NaZn 4 Sb 3 , HT -Na 1– y Zn 4– y Sb 3 , KZnSb, K 8– x Zn 18+3 x Sb 16 , K 58 Zn 122 Sb 207, Cs 8 Zn 18 Sb 28 , CsZnSb, RbZnSb, and Rb 2 Zn 5 Sb 4 . , ,− Among these, Cs 8 Zn 18 Sb 28 is the first antimony-based clathrate I, K 58 Zn 122 Sb 207 represents novel clathrate XI, and LiZnSb was theoretically predicted to show remarkable thermoelectric performance, e.g ., ability to convert heat into electricity and vice versa . Remarkably, inexpensive and nontoxic binaries (Zn 4 Sb 3 , Zn 13 Sb 10 , Zn 8 Sb 7 , Zn 3 Sb 2 , ZnSb) and ternary zinc (or cadmium) antimonides (family of Ae (Zn/Cd) 2 Sb 2 compounds ( Ae = Ca, Sr, Ba, Eu, or Yb), Eu 2 ZnSb 2 , and Ca 9‑y Eu y Zn 4+x Sb 9 ) as well as other related Zintl phases attract attention for their thermoelectric properties. , For that reason, a comprehensive investigation of the unexplored A –Zn-Sb systems is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the guest atoms or vacancies can suppress the lattice thermal conductivity by strengthening phonon scattering [22][23][24]. Indeed, high thermoelectric efficiency has been realized in some Zintl phases, such as YbZn 2 Sb 2 [25,26], Ca 9 Zn 4.5 Sb 9 [27,28], Ca 5 Al 2 Sb 6 [29], and Yb 14 MnSb 11 [30]. Our previous studies reported the thermoelectric performance of the ZrBeSi-type Zintl-phase Eu 2 ZnSb 2 , and a ZT value of 1.0 was achieved at 823 K [31].…”
Section: Introductionmentioning
confidence: 99%